ANALISIS PERBANDINGAN MODEL ALTMAN, SPRINGATE DAN ZMIJEWSKI DALAM MEMPREDIKSI KEBANGKRUTAN - Rita Purnama Sari (STIE AUB Surakarta, 2018)
This study aims to identify and provide empirical evidence: 1) There are differences in potential bankruptcy in Food and Beverages companies using Altman, Springate and Zmijewski methods, 2) The most accurate prediction model in predicting bankruptcy of Food and Beverage companies, 3) Food and Beverages which is predicted to be bankrupt. Sampling using purposive sampling technique and obtained 13 companies. This study uses secondary data on Food and Beverages company listed in Indonesia Stock Exchange (BEI) period 2014-2016. Hypothesis testing using technique analysis tool One Way Anova Test Kruskal-Wallis Test and Mann-Whitney Test. The test results show that there are significant differences between the three models in predicting bankruptcy. Altman method has the highest accuracy rate of bankruptcy calculation, so the Altman method is the most effective method used to predict the potential bankruptcy in the company Food and Beverages. Based on the most accurate method, Altman Z-Score potential bankrupt is AISA, ALTO and PSDN.Keywords: Food and Beverages Company, Bankruptcy, Altman, Springate, Zmijewski